The role of stakeholders in the sustainability of the Simantri program in Tabanan - I Dewa Ayu Made Natasah Dewani; Ida Ayu Nyoman Saskara; Ni Putu Wiwin Setyari (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The current development of the agricultural sector requires the involvement of stakeholders from various circles. The role of stakeholders is adjusted to the duties and responsibilities they have so that the results achieved can run optimally. This study aims to identify the typology of actors based on the strengths and relationships between actors and the attitudes of actors towards the sustainability goals of the Simantri program. Data collection methods in this study were interviews, questionnaires, and Focus Group Discussions (FGD). Data analysis used the Mactor method (Matrix of Alliances and Conflicts Tactics, Objectives, and Recommendations). The results showed that the Bali Provincial Agriculture Office and Tabanan Regency Agriculture Office were the dominant actors. Agricultural Extension Agency (BPP), Farmer's Cooperatives, Financial Institutions, PKK, and fertilizer collectors are relay actors, and Hotels/Restaurants are dominated, actors. Most of the stakeholders converge in supporting the strategic goals to be achieved. This finding becomes the basis for developing a pattern of collaboration between all stakeholders that is needed for the sustainability of the Simantri program.